Kepuasan pernikahan pada perkawinan matrilineal: Bagaimana peranan keterbukaan diri dan kematangan emosi? (SUKMA : Jurnal Penelitian Psikologi, 2022)
This study uses a quantitative correlational research design to determine (1) the relationship between self-disclosure and emotional maturity with marital satisfaction in matrilineal marriages in Ngada District (2) the relationship between self-disclosure and marital satisfaction in matrilineal marriages in Ngada District (3) the relationship between emotional maturity and marital satisfaction of husband and wife in matrilineal marriages in Ngada District. Sampling in this study using non-probability sampling using purposive sampling technique. The population in this study were married couples in Ngada Regency who were married in a matrilineal manner with a minimum age of 5 years of marriage. The subjects of this study amounted to 102 people. The analysis technique uses multiple regression analysis to determine the direction and influence of self-disclosure and emotional maturity on marital satisfaction in matrilineal marriages in Ngada District. Measuring tools used in the form of a scale of marital satisfaction, a scale of self-disclosure and a scale of emotional maturity. The results of this study reveal that self-disclosure and emotional maturity have a significant influence on marital satisfaction in matrilineal marriages in Ngada District, both partially and simultaneously.